PERAWATAN LUKA PADA KORBAN GEMPA DI KP. CIPETIR, DESA CIWALEN, KEC. WARUNGKONDANG CIANJUR, PROVINSI JAWA BARAT - Juairiah Juairiah; Dea Aprilya; Rini Rahmasari (JPS : Jurnal Pengabdian Serulingmas, 2023)
Geologically, Indonesia is in a disaster-prone area, because Indonesia is located on three tectonic plates in the world, namely: the Indo-Australian Plate in the south, the Euro-Asian Plate in the north and the Pacific Ocean Plate in the east so that Indonesia is at high risk of experiencing earthquakes. Earthquakes can damage various infrastructure and endanger lives. One of the earthquakes that occurred in Cianjur, West Java Province resulted in many victims, especially in Kp. Cipetir, Ciwalen Village, Kec. Warungkondan who suffered minor to serious injuries because of being crushed by the ruins of the building. Update data on injured victims from the "Telapak Kaki Nusantara" Community, which has provided services for 3 weeks in the village, obtained data on a total of 234 minor injured patients, 70 seriously injured and 8 broken bones. The Sumber Waras STIKes institution as an education provider in carrying out the tridharma of higher education was moved to carry out community service activities for the Cianjur earthquake victim group by carrying out wound care activities due to the impact of the collapsed building. The aims of this community service program are provide wound care to the earthquake casualties to optimize the healing process and improve their quality of life. Wound care is a technique to prevent infection, kill or inhibit the growth of germs and bacteria that can interfere with the wound healing process. The result of this program is wound care for 6 patients with various severity wound. The follow up planning for this program is the continuity care is given to health care volunteers who remain on the site.